'I want to be one of them': a study using photovoice to explore the inequities of floating children in China. Issue 4 (4th July 2021) - Tang, Yong
ABSTRACT: The photovoice process aims to use photographic images taken by persons from deprived backgrounds to enhance community needs assessments, empower participants, and induce change by informing policy makers of community assets and deficits. This article describes a project on the photovoice of floating children's (internal migrant children's), implemented through a community programme to highlight education and health inequalities. The data were collected through in-depth interviews that were evaluated through a thematic analysis. Three major themes were identified from the children's own words: (1) rural habitus (2) cultural capital constraints and (3) social support. This study provides interesting preliminary insights into the lives of floating children, which could help inform the development of interventions and bring about positive educational and environmental changes for this marginalised population.